Research note: The global economic crisis: Impact on Indian outward investment - Jaya Prakash Pradhan (Transnational Corporations, 2011)
This article reviews the emerging trends of outward investment flows from India in the period of global slowdown and presents the preliminary findings on the changing behaviours of emerging Indian transnational corporations (TNCs). It shows that during the early 2000s, Indian outward investment registered a faster and sustained growth as an increasing number of Indian firms turned to the global market for growth, technologies and natural resources. However, it displayed a decline in 2008 and the first half of 2009. The global financial and economic crisis appears to have seriously dented overseas expansion plans of emerging Indian TNCs. Indian investment slowdown considerably as Indian firms are faced with declining domestic demand, falling exports, rising debt burden, uncertain and difficult financial markets, and a volatile exchange rate. Deteriorating profit and sales levels of their overseas affiliates are found to have negative impacts on the global performance of a number of Indian TNCs. Nevertheless, as global assets have become cheaper in the crisis period and there are signs of recovery in the domestic demand, Indian foreign investment could regain its growth dynamism in the coming few years.